2021
DOI: 10.1177/00169862211032987
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being of Intellectually and Academically Gifted Students in Self-Contained and Pull-Out Gifted Programs

Abstract: This study examined the psychological well-being of students enrolled in two gifted programs with different service delivery models. Participants were 292 fifth- and sixth-grade students ( Mage = 11.70, SDage = 0.65) enrolled in a gifted math pull-out program ( n = 103), a self-contained gifted program ( n = 90), or a program providing no gifted services, which served as a control group ( n = 99). Multiple differences in psychological well-being across programs were revealed in Hierarchical Linear Models, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 118 publications
0
3
0
1
Order By: Relevance
“…Research examining loneliness in gifted children and adolescents is rather limited and beneficial solitude in this portion of youth has hardly attracted any research attention. There is evidence supporting the view that loneliness is high in gifted children and adolescents, when giftedness is mainly conceptualised as high intelligence (Kaiser and Berndt, 1985;Woodward and Kalyan-Masih, 1990;Cash and Lin, 2022). It has also been found that gifted children and adolescents have a sense of being different from other children (Janos et al, 1985a), they feel that they do not have enough friends, have difficulties in making friends (Janos et al, 1985b) and are rejected more frequently than nongifted children (Luftig and Nichols, 1990).…”
Section: Loneliness and Solitude In Gifted Children And Adolescents: ...mentioning
confidence: 91%
“…Research examining loneliness in gifted children and adolescents is rather limited and beneficial solitude in this portion of youth has hardly attracted any research attention. There is evidence supporting the view that loneliness is high in gifted children and adolescents, when giftedness is mainly conceptualised as high intelligence (Kaiser and Berndt, 1985;Woodward and Kalyan-Masih, 1990;Cash and Lin, 2022). It has also been found that gifted children and adolescents have a sense of being different from other children (Janos et al, 1985a), they feel that they do not have enough friends, have difficulties in making friends (Janos et al, 1985b) and are rejected more frequently than nongifted children (Luftig and Nichols, 1990).…”
Section: Loneliness and Solitude In Gifted Children And Adolescents: ...mentioning
confidence: 91%
“…The 10% most talented students in each cohort are eligible to participate in the enrichment program, meaning that the program is less selective than programs that follow a traditional, narrower academic giftedness definition, which targets only the top 2% or an even smaller proportion of students 9 . The Hector Children's Academy Program is also broader in its inclusion criteria than programs that—in the tradition of Terman 10 —primarily rely on psychometric intelligence (for an example, see Cash and Lin 11 ). This more inclusive approach is in line with theoretical conceptions 2 that emphasize the developmental aspects in children's cognitive and creative biographies.…”
Section: The Hector Children's Academy Programmentioning
confidence: 99%
“…Itu berarti tinggi rendahnya psychological well being individu, tergantung dari bagaimana individu itu sendiri secara efektif dapat mengatur sumber-sumber sekitarnya baik internal maupun eksternal dalam memaksimalkan tingkat fungsional. Menurut (Cash & Lin, 2022) psychological well-being merupakan evaluasi positif seseorang terhadap diri mereka sendiri dan pengalaman hidup mereka (misalnya, konsep diri, harga diri), kesehatan psikologis (misalnya, perfeksionisme), dan hubungan dengan orang lain (misalnya, kesepian, sikap terhadap lingkungan dan pekerjaan).…”
Section: Psychological Well-beingunclassified